Zonal Mapping of Risk Information Model of Construction in Laterite Soil - Bhagyashree *, Kavyashree (International Journal of Advanced Science and Technology, 2020)
The present study is an experimental investigation on the geotechnical properties of soil samples relevant to construction industry.  The main point of view of the study is to understand the characteristics of soil samples before carrying out of any construction on it which is essential too. These papers summarize the characteristics of laterite and its suitability for the construction of high-rise buildings on it.For this the samples were collected from nine different places which are nearby to each other in the coastal belt of Dakshina Kannada district. Geotechnical tests were performed that includes all the preliminary tests to be conducted on the soil. Construction Risk Management is considered to be the integral part of any construction project and it is achieved by forming risk matrix. Five Point Likert scale is used to categorise the risks from very high to very low. Safe Bearing Capacity of soil is considered for the above calculations.